2021
DOI: 10.1021/acs.langmuir.0c03079
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Structural Dynamics of the Coil–Globule Transition of Thermosensitive Nanocomposite Hydrogels

Abstract: Nanocomposite hydrogels have emerged to exhibit multipurpose properties, boosting especially the biomaterial field. However, the development and characterization of these materials can be a challenge, especially stimuli-sensitive materials with dynamic properties in response to external stimuli. By employing UV–vis spectroscopy and NMR relaxation techniques, we could outline the formation and behavior of thermosensitive nanocomposites obtained by in situ polymerization of poly­(N-vinylcaprolactam) (PNVCL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 78 publications
(163 reference statements)
1
22
0
Order By: Relevance
“…Sala et al 21 also reported a decrease in the transition enthalpy with the insertion of 1% and 5% of silica nanofibers. However, it is possible to see in Table 2 that there is no statistical difference between nanocomposites synthesized with 1% and 5% of silica nanospheres with 80 and 330 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Sala et al 21 also reported a decrease in the transition enthalpy with the insertion of 1% and 5% of silica nanofibers. However, it is possible to see in Table 2 that there is no statistical difference between nanocomposites synthesized with 1% and 5% of silica nanospheres with 80 and 330 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…This behavior can be correlated to changes in the solvation of the polymer−silica system and thereby the hydrophilic/hydrophobic interactions during the coil−globule transition, as previously demonstrated. 21 The entropy of a mixture of the PNVCL solution is decreased with an increase in temperature, causing the polymer chains to start to agglomerate, leading to phase separation. The presence of nanoparticles in the polymeric matrix may disrupt the interaction between the water molecules and the polymer chains, facilitating the agglomeration of globules at temperatures below the T cp , decreasing the transmittance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wetting behavior changed from hydrophilic to hydrophobic as the cross-linker quantity was increased, owing to increased and close packing that changed surface characteristics. Because of the dense packing and higher cross-linking, there is less hydrogen bonding available to create functional groups ( Sala et al, 2021 ). As a result, the hydrogel sample (AGP-1) was found to have the highest hydrophilicity (64.50°) with minimal cross-linking and the highest hydrophobicity (AGP-4) with maximal cross-linking (110.80°) as presented in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%